A Curated Debate: On Using "Templates" in Qualitative Research. (July 2022) - Gioia, Denny; Corley, Kevin; Eisenhardt, Kathleen; Feldman, Martha; Langley, Ann; Lê, Jane; Golden-Biddle, Karen; Locke, Karen; Mees-Buss, Jacqueline; Piekkari, Rebecca; Ravasi, Davide; Rerup, Claus; et al.
One of the raging debates in organization study concerns the use of "templates" in qualitative research. This curated debate brings together many of the players in that debate, who make statements of position relative to the issues involved and trade accusations and counter-accusations about statements they have made that in their view have been misinterpreted or misconstrued. Overall, it is quite a lively debate that reveals positions, points of tension and grounds for disagreement. Denny Gioia wrote the triggering essay that prompted other players to weigh in with their personal and professional views.